Awareness of Cervical Cancer among Staff Nurses in a Tertiary Level Cancer Centre in Bangladesh - Bardhan, Sushmita; Pervin, Shahana; Mazumder, Suzon Kumar (Bangladesh Journal of Obstetrics & Gynaecology, 2022)
Background: Cervical cancer is the second leading malignancy and cause of death in Bangladeshi women. Health professional’s misconceptions about the disease and lack of knowledge may worsen the situation. Nurses form a large proportion of the health care provider workforce. Among them who had opportunity to work in cancer hospital should know better about cervical cancer than other hospitals in the country. This survey was undertaken with an intention to address this important health issue by determining the awareness of cervical cancer among nurses at a tertiary cancer centre of Bangladesh. Objective: To provide the baseline information about the knowledge of cervical cancer and explore attitude and practice of cervical cancer screening among staff nurses. Methods: A pretested structured self-administered questionnaire based cross sectional survey was done on 154 staff nurses working in National Institute of Cancer Research and Hospital (NICRH), Dhaka, containing mostly recognition and some recall type questions about knowledge of cervical cancer, its risk factors, screening techniques, attitude towards cervical cancer screening and its practices. Results: 100% respondents heard the name of cervical cancer but 35.7% did not know about any of its risk factors and only 3.2% aware about more than 3 risk factors. Twenty seven percent not aware about any symptom, only 51.9% identified the foul smelling excessive vaginal discharge and irregular abnormal vaginal bleeding as the symptom and 16.8% know that post coital bleeding may be the symptom. Only 42.2% know VIA as a screening test, 39.6% know actual screening interval, 23.37% know who should be screened, 42.2% aware about HPV vaccine, 35.7% can do VIA, 42.2% said that they referred patient for screening but only 16.2% of themselves have ever been screened. Conclusion: The majority of nursing staff in NICRH had inadequate knowledge about cervical cancer screening and their attitude and practice towards cervical cancer screening could not be termed positive. There is an urgent need for orientation course for working nurses and integration of cervical cancer prevention issues in the existing curriculum of nurses in Bangladesh. Bangladesh J Obstet Gynaecol, 2020; Vol. 35(2): 102-106